Does Design Rationale Enhance Creativity? - Wang, Jing; Farooq, Umer; Carroll, John (Human Technology, 2010)
Creativity and rationale are often viewed as two contrasting facets in software design. A lack in recognizing the facilitative relationship between creativity and rationale not only underestimates the benefits designers can obtain from rationale practices, but also confines the approaches that support creativity in software design. Our exploratory study provides empirical evidence of the positive correlation between rationale and creativity. Furthermore, we found that the feasibility of design alternatives and the comprehensiveness of tradeoff evaluation are critical to enhancing novelty, persuasiveness, and insightfulness. We also discuss future directions to further understand how these properties, or rationale quality in general, affects design creativity.